Sequential Milkrun System - ÖZHAN DOĞAN, Serap; Ahmet KARATAŞ; Mücahit DEMİRCİOĞLU (International Journal of Computational and Experimental Science and Engineering, 2024)
Milk-Run system is a logistics supply method that aims to combine and place the products or materials required by companies into vehicles in the most efficient way. This system collects goods from multiple suppliers and ensures that vehicles are filled at an optimum level. It ensures controlled management of transactions with regular reporting, continuous monitoring and automatic information e-mails. Within the scope of the study, important processes related to the Milk-Run management process were emphasized and the reasons for the application were highlighted. Logistics and supply chain have played important roles in supporting the operations of businesses aiming to meet customers’ demands. It is a sustainable management model that helps all businesses that implement it reduce their costs, optimize their processes and reduce their carbon footprint.